In-vitro and in-vivo combined effect of ARQ 092, an AKT inhibitor, with ARQ 087, a FGFR inhibitor - Yu, Yi (Anticancer Drugs, 2017)
The PI3K/AKT pathway plays an important role in the initiation and progression of cancer, and the drug development efforts targeting this pathway with therapeutic interventions have been advanced by academic and industrial groups. However, the clinical outcome is moderate. Combination of inhibition of PI3K/AKT and other targeted agents became a feasible approach. In this study we assessed the combined effect of ARQ 092, a pan-AKT inhibitor, and ARQ 087, a pan-FGFR inhibitor, in vitro and in vivo. In a panel of 45 cancer cell lines, on 24% (11 out of 45) the compounds showed synergistic effect, on 62% (28 out of 45) additive, and on 13% (6 out of 45) antagonistic. The highest percentage of synergism was found on endometrial and ovarian cancer cell lines. Mutational analysis revealed that PIK3CA/PIK3R1 mutations and aberrant activation of FGFR2 predicted synergism, whereas Ras mutations showed a reverse correlation. Pathway analysis revealed that a combination of ARQ 092 and ARQ 087 enhanced the inhibition of both the AKT and FGFR pathways in cell lines in which synergistic effects were found (AN3CA and IGROV-1). Cell cycle arrest and apoptotic response occurred only in AN3CA cell, and was not seen in IGROV-1 cells. Furthermore, enhanced antitumor activity was observed in mouse models with endometrial cancer cell line and patient-derived tumors when ARQ 092 and ARQ 087 were combined. These results from in-vitro and in-vivo studies provide a strong rationale in treating endometrial and other cancers with the activated PI3K/AKT and FGFR pathways.